Malformação congênita associada à síndrome do Zika vírus: a microcefalia e o papel da enfermagem – uma revisão integrativa de literatura - SILVA, Risângela Patrícia de Freitas Pantoja da (2020)
Objective: This study aims to understand the mechanism by which the Zika virus crosses the hematoplacental barrier, to understand the relationship of the virus and its predilection for the cells of the Central Nervous System, to describe the neurological diseases caused by the Congenital Syndrome of the Zika Virus and discuss the the role of the nurse in front of the new national panorama. Method: This research used the method of Integrative Literature Review, through the search in specialized databases of VHL and Multidisciplinary Web of Science in the following indexers: LILACS; MEDLIDE and SCIELO. The following descriptors (DeCS) were defined: zika virus; microcephaly; nursing. We used the Boolean operator AND in the Portuguese and English languages on the subject proposed for study. Results: The sample of this study was composed of 23 national publications and 25 international ones, and after exhaustive reading, thorough analysis and categorization of the articles, three categories were identified: "How is the passage of the virus through the placenta. "," The Teratogenic Consequences Related to Zika Virus Exposure "and" The Importance of Nurses for Reducing Diseases. " Conclusion: Considering the growth of the cases of microcephaly associated with the congenital syndrome of the Zika virus and its increasingly alarming aggravation, nursing plays an extremely important role, which aims to offer the user a quality nursing care based on Law no. 7.498 / 96 in the Code of Ethics of Nursing Professionals, aiming to ensure continuity of care at all levels of care. However, it is essential that nurses have the desired technical and scientific skills to provide adequate care, and a relationship based on respect and trust for the user is essential to provide comfort and safety. The results of this research show that, although there is an increasing number of studies proving the association of the Zika virus in the gestational period with microcephaly, there is still a need for more studies especially in nursing, where little has been present at the core of the scientific society as well as was not observed enough scientific production on the work process and nursing actions in face of this aggravation.